THE COST OF NUTRITION ALTERNATIVES FOR PREMATURE INFANTS IN RUSSIA - K. V. Gerasimova; M. V. Avxentyeva; I. A. Belyaeva (Фармакоэкономика, 2016)
Objective – to perform economic evaluation of clinical breast pump for inpatient premature infants breastfeeding. Methods. The cost of providing 100 ml of breast milk (BM) using clinical breast pump and 100 ml of artificial formula (AF) for premature infants were calculated. The total cost of providing BM was measured as: the breast pump cost, the individual pumping set cost and staff costs. The cost of providing AF was calculated using the mean cost per 100 ml for powdered AF and staff costs. Also the cost per averted case of necrotizing enterocolitis (NE) for premature infants when breastfeeding instead of the AF was calculated. The cost of the averted NE was obtained using the difference in cost of feeding during the period, required for NE development and number of patients “needed to treat” (NNT) to prevent 1 NE case derived from the clinical trials. Besides we calculated the BM cost when BM fortifier is added for low-weight infants, the BM cost with the use of another model of clinical breast pump and the cost of liquid AF. Sensitivity analyses of the calculation results to fluctuations in the cost of AF, breast pump, individual pumping set and staff salaries size was conducted. Results. The costs per 100 ml of BM and AF were similar (47.17 и 41.14 rubles, respectively). The cost per averted case of NE was 21 115 rubles within 35 days that is less than NE treatment. The use of the more expensive breast pump model did not affect the results significantly (the difference in cost (in favor of AF) increased by 2 rubles per 100 ml and was 8 rubles per 100 ml). The use of BM fortifier increased the cost of BM up to 176 rubles per 100 ml. The results were mostly sensitive to the individual pumping set and AF costs fluctuations: sensitivity analysis showed that BM became more cost-effective when the price of powdered AF was over 937 rubles per package. Conclusion. The cost of BM is comparable to the cost of AF, with a significant BM clinical benefit.